Central nervous system relapse in high-risk stage 4 neuroblastoma: The HR-NBL1/SIOPEN trial experience. (February 2021) - Berlanga, P.; Pasqualini, C.; Pötschger, U.; Sangüesa, C.; Castellani, M.R.; Cañete, A.; Luksch, R.; Elliot, M.; Schreier, G.; Kropf, M.; Morgenstern, D.; Papadakis, V.; et al.
Abstract: Background: There is rising concern on the impact of new strategies, such as high-dose chemotherapy (HDC) and immunotherapy, on the pattern of relapse in high-risk neuroblastoma (HR-NBL). Our aim is to evaluate the incidence and identify risk factors for first recurrence in the central nervous system (CNS) in HR-NBL. Patients and methods: Data from patients with stage 4V HR-NBL included from February 2002 to June 2015 in the prospective HR-NBL trial of the European International Society of Pediatric Oncology Neuroblastoma Group were analysed. Characteristics at diagnosis, treatment and the pattern of first relapse were studied. CNS imaging at relapse was centrally reviewed. Results: The 1977 included patients had a median age of 3 years (1 day–20 years); 1163 were boys. Among the 1161 first relapses, 53 were in the CNS, with an overall incidence of 2.7%, representing 6.2% of all metastatic relapses. One- and three-year post-relapse overall survival was 25 ± 6% and 8 ± 4%, respectively. Higher risk of CNS recurrence was associated with female sex (hazard ratio [HR] = 2.0 [95% confidence interval CI: 1.1–3.5]; P = 0.016), MYCN -amplification (HR = 2.4 [95% CI: 1.2–4.4]; P = 0.008), liver (HR = 2.5 [95% CI: 1.2–5.1]; P = 0.01) or >1 metastatic compartment involvement (HR = 7.1 [95% CI: 1.0–48.4]; P = 0.047) at diagnosis. Neither HDC nor immunotherapy was associated with higher risk of CNS recurrence. Stable incidence of CNS relapse was reported over time. Conclusions: The risk of CNS recurrence is linked to both patient and disease characteristics, with neither impact of HDC nor immunotherapy. These findings support the current treatment strategy and do not justify a CNS prophylactic treatment. Highlights: In high-risk neuroblastoma the impact of treatment on the relapse pattern is unknown. Central nervous system (CNS) recurrences have an overall incidence of 2.7%. They represent 6.2% of all metastatic relapses. The incidence of CNS recurrences is stable over time. Neither high-dose chemotherapy nor immunotherapy has increased CNS recurrence.